Edukasi Pengetahuan Orang Tua Tentang Diabetes Melitus (DM) dan Screening Risiko DM pada Anak Usia Sekolah di SD Negeri 1 Dukuhwaluh - Nudin, Jauhar; Wirakhmi, Ikit Netra; Khasanah , Suci (Lembaga Pengembangan Kinerja Dosen, 2025)
The rising prevalence of Diabetes Mellitus (DM) among children highlights the need for early intervention, particularly through parental education and lifestyle supervision. This study aimed to improve parents’ knowledge about DM and conduct risk screening for school-aged children at SD Negeri 1 Dukuhwaluh. The program was carried out through health education sessions for 70 parents using pre-test and post-test assessments, and health screening for students in grades 4 to 6, involving random blood glucose tests, BMI measurement, and identification of classic DM symptoms. The results showed a significant increase in parental knowledge, with those in the